2004
DOI: 10.1377/hlthaff.23.4.42
|View full text |Cite
|
Sign up to set email alerts
|

Caring For Patients In A Malpractice Crisis: Physician Satisfaction And Quality Of Care

Abstract: The rhetoric of malpractice reform is at fever pitch, but political advocacy does not necessarily reflect grassroots opinion. To determine whether the ongoing liability crisis has greatly reduced physicians' professional satisfaction, we surveyed specialist physicians in Pennsylvania. We found widespread discontent among physicians practicing in high-liability environments, which seems to be compounded by other financial and administrative pressures. Opinion alone should not determine public policy, but physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(69 citation statements)
references
References 13 publications
5
64
0
Order By: Relevance
“…This is consistent with their later results (Mello et al 2005) that suggest that Pennsylvania specialists have scaled back their practices and are more likely to retire early as a result of liability exposure. Their results also indicate that this has led to a reduction in access to care for patients in Pennsylvania.…”
Section: Previous Studies Of Reform and Physician Supplysupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with their later results (Mello et al 2005) that suggest that Pennsylvania specialists have scaled back their practices and are more likely to retire early as a result of liability exposure. Their results also indicate that this has led to a reduction in access to care for patients in Pennsylvania.…”
Section: Previous Studies Of Reform and Physician Supplysupporting
confidence: 89%
“…Taking a different approach, Mello et al (2004) surveyed specialists in Pennsylvania and found that their professional satisfaction is negatively related to liability exposure. This is consistent with their later results (Mello et al 2005) that suggest that Pennsylvania specialists have scaled back their practices and are more likely to retire early as a result of liability exposure.…”
Section: Previous Studies Of Reform and Physician Supplymentioning
confidence: 99%
“…Other evidence indicates that the impact of the crisis on physicians was considerable, in terms of costs, anxiety, and disillusionment with the practice of medicine. 32 Statewide, however, physicians appear to have held their ranks and weathered this distress.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' complaints are experienced by doctors as a challenge to their expertise and as a potential threat to their professional identity (Marjoribanks et al 1996;Allsop and Mulcahy 1998). Several studies suggested that medical encounters have been deeply altered by a growing litigious environment, since the trusting patient was replaced by a threatening or confrontational patient (Mello et al 2004;Jacques 2007), resulting in strained doctor-patient relationships (Cook and Neff 1994). For example, it has been said that increased physicians' liability degraded the traditional trust-based doctor-patient relationship (Vanderminden and Potter 2010).…”
Section: Legal Challenge and Patients' Complaintsmentioning
confidence: 99%